Corporate reliance on bank loans: A case study on property and construction sectors in Malaysia / Bibiwana Asaari - Asaari, Bibiwana (2007)
The focus of this research study was the widespread use of bank borrowings by companies in 2 sectors namely property and construction sectors which are listed in Main Board of Bursa Malaysia, within 5 years period ranged from 2001 until 2005. The objectives of this research study consist of 3 parts. Firstly, this research study has been conducted to overview those companies' reliance on bank loans as a source of financing. Therefore, two sets of Descriptive Statistics method have been used and the results suggested that, on average, bank loans acquired by both sectors constitute almost half of their outstanding debt. Secondly, this research study has been done to identify factors that might influent those companies' preferences on bank loans. In this respect, Multiple Regression method has been employed in order to test whether potential factors such as firms' size, age, leverage and interest rate would have significant influence on the companies' bank debt ratio. The result revealed that firms' age was one of the determinants of bank loans preference and it was positively related. Moreover, this study also observed that construction companies' leverage situation had a strong positive effect on its bank debt ratio. In contrast, property companies' leverage has been explained to be negatively related with its bank debt ratio. However, this research study failed to provide evidences showing firms' size and interest rate to have significant effect on both developers and contractors' decision to demand for bank loans as a source of financing. Lastly, this study also has been done to compare both sectors' reliance on bank loans and it was proven that actually, there was no significant difference of preferences on bank loans between the property and construction sectors in Malaysia during the period of 2001 until 2005.